Decarbonizing Indian Electricity Grid - Parvathy Sobha (arXiv.org, 2022)
India, being one of the fastest growing economies of the world, must take a sustainable path for development. India is responsible for 7 percent of global CO2 emissions. The electricity sector accounts for nearly 35 percent of emissions from the country. The switch from fossil fuels to renewable sources is the key in decarbonizing this sector and is considered as the crucial step for climate mitigation. This research investigates the potential of renewable energy sources; wind, solar and hydro. The optimization model developed in this study analyzes various scenarios for the transition to a sustainable future. The results show that India aims to achieve 450 GW of installed capacity from RES is far from a Net Zero future. Results confirm that India has the potential to meet 100 percent of electricity demand in 2030 from RES including wind, solar and hydro. Introducing Social Cost of Carbon is a viable option to reduce emissions in India. However, due to the low cost of coal, high coal taxes do not lead to reduced emissions.